2018
DOI: 10.1001/jamasurg.2018.0087
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Real-time Electronic Injury Surveillance Applications and Clinical Documentation and Data Acquisition in a South African Trauma Center

Abstract: Accurate capture and simultaneous analysis of trauma data in low-resource trauma settings are feasible through the integration of surveillance into clinical workflow and the timely analysis of electronic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…We can help build data collection infrastructure by exporting electronic registries applicable to low-resource settings. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can help build data collection infrastructure by exporting electronic registries applicable to low-resource settings. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…We can help build data collection infrastructure by exporting electronic registries applicable to low-resource settings. 27,28 The culmination of successful academic partnerships is coauthorship in research publications. It is disappointing that some GSPs do not result in published recognition of contributing partners.…”
Section: Bilateral Authorshipmentioning
confidence: 99%
“…Nonetheless, the ingredients for successful trauma registry implementation that have been well-documented in the literature, including local stakeholder buy-in, a motivated workforce, and secure funding, were crucial elements in the development, implementation, and ongoing presence of the SRRH registry. One way to address its shortcomings might be to transition away from the use of paper, as numerous studies have noted the high rates of data completeness and correctness associated with electronic trauma registries [ 30 ]. Unfortunately, their implementation is not yet feasible in a setting like rural Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the use of spatial data to identify injury hotspots within the context of the built environment has potential to be especially beneficial for informing prevention efforts. [29][30][31] For example, in rural Kenya, a health center-based injury surveillance system that incorporated GPS data was able to identify environmental correlates at the locations of injuries through geographic information systems (GIS) software and analyses. 31 Distance to major roads proved to be a major determinant of injury in this area.…”
Section: Opportunitiesmentioning
confidence: 99%
“…29 49 In one case, missing data were reduced by 25% on average from a previous paper-based charting system. 29 Data collectors have found that the apps developed for these purposes are easier and quicker to populate compared with paper-based methods, often making use of convenient drop-down menus or prompts that remind the user of a blank field. 29 49 50 Furthermore, the capability for a system administrator to view data-entry in real time has improved quality control efforts and, consequently, data compliance.…”
Section: Challengesmentioning
confidence: 99%